Sistem Pemantauan Daya pada Wireless Sensor Network menggunakan Algoritma Priority Scheduling - Muhammad Ihksan Sahib Latif; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wireless Sensor Network is a wireless technology required for monitoring environmental conditions which consist of several sensor nodes that can communicate and process information with each other. The problem in WSN is about power consumption which results in power at the node using only batteries for its operation, resulting in limited energy reserves. When one node dies, it results in a change in performance, there is an obstacle in having to conserve power energy repeatedly and reduce the benefits of WSN. The solution to this problem is to implement the Priority Scheduling algorithm to be placed on each node which will prioritize the order based on the largest to the smallest power. In the power monitoring mechanism of each node, NRF24L01 is available for sending and receiving data, Arduino Uno R3 microcontroller, ACS712-30A current sensor, voltage sensor, DHT11, and RTC DS1307 which functions to display real-time data results. Based on the test results, DHT11 accuracy is 98.52% to 99.26%, voltage accuracy is 99.6%, and the current accuracy is 94.86% to 97.86%. Data reception performance takes an average of 2 to 3 seconds. Retrieval of power data using Priority Scheduling in the room there are obstacles and no obstacles have a 100% success percentage obtained by looking at the results of the power data displayed on 10 experiments in different rooms and the order is according to the largest to the smallest power data.